Path Loss and Shadowing Characterization for Forest Environment - Piotr GAJEWSKI (Communications of International Proceedings, 2021)
This paper focuses on the propagation characteristics of the forest environment based on measurements made in the vicinity of Warsaw. In the paper, we present the structure of the test-bed, scenario, and results of the performed measurements. Measurements were made for several frequencies in the very-high (VHF) and ultra-high frequency (UHF) bands on which military systems operate. Based on the level of the received signal, we determined the path loss models and the shadowing parameter. The determined propagation model is one of the elements that will be used in the created radio environment map (REM) for the emerging military communication system.
Keywords: Radio Environment Map (REM); Path Loss; Shadowing; Forest Environment.